Evolution over time of the effects of fiscal shocks in the peruvian economy: empirical application using TVP-VAR-SV models - Meléndez Holguín, Alexander; Rodríguez, Gabriel (Pontificia Universidad Católica del Perú. Departamento de Economía, 2023)
This study assesses the evolving impact of fiscal policy on Peru’s economic activity in 1993Q4-2018Q2 using unrestricted and restricted TVP-VAR-SV models according to the approach proposed by Chan and Eisenstat (2018a). The results indicate that SV inclusion is essential, although there is no clear evidence of time-varying parameters according to two Bayesian selection criteria. Shocks from current and capital spending growth have positive effects on GDP growth (0.2% and 0.3%, respectively, in response to a 1% increase in each variable); and play important roles in the forecast error variance decomposition (23% and 45%, respectively) and historical decompositon (14% and 25%, respectively). The impact of fiscal income shocks is weak throughout the period of the study. The current and capital spending multipliers grow in 1995Q1-2007Q4, but subsequently show lower values in 2008Q1-2018Q2. The study also finds that external shocks have a strong and positive impact on fiscal income growth (0.4%). Finally, the research includes multiple robustness exercises, which show few changes relative to the results obtained using the baseline model.
Keywords: Fiscal Policy; Fiscal Multiplier; VAR Model with Time-Varying Parameters; Stochastic Volatility; Bayesian Estimation; Peruvian Economy; https://purl.org/pe-repo/ocde/ford#5.02.01